MGlu receptors (Humana Press, 2017)
Metabotropic glutamate receptors (mGluRs) are members of the group C family of G-protein-coupled receptors. Eight different mGlu subtypes have been identified and classified into three groups based on amino acid sequence similarity, agonist pharmacology, and the signal transduction pathways to which they couple. They perform a variety of functions in the central and peripheral nervous systems, being involved in learning, memory, anxiety, and the perception of pain. They are found in pre- and postsynaptic neurons in synapses of the hippocampus, cerebellum, and cerebral cortex, as well as other parts of the brain and peripheral tissues. This volume comprises the latest contributions of experts in the field on the role of mGlu receptor in health and disease, following the 8th International meeting on these receptors.
Keywords: Drug addiction.; Cocaine.; Glutamic acid -- Receptors -- Effect of drugs on.; Dopamine.; elektronické knihy; electronic books